(untitled) (Research, Society and Development, 2024)
This article addresses the topic of 5G and 6G as a Technological Innovation System (TIS) along with the industrial application of Remote Surgery as an empirical case, exploring three main contributions. Firstly, this research contributes to the connection of the Technological Innovation Systems perspective and 5G and 6G networks in a quantitative viewpoint at national and international levels. Secondly, it contributes to Knowledge Production (F2) and Diffusion (F3) studies through Bibliometrics and software uses. Third, it contributes to the studies of a connection in 5G and 6G networks in the Remote Surgery empirical case application on TIS analytical background. Methodologically, the research problem of this study is to explore the R&D capacity in 5G and 6G TIS concerning the applicability of Remote Surgery worldwide and, consequently, in Germany. The general objective is to improve the industrial relevance of Remote Surgery through quantifying publications and patents and the collaborative networks in these domains. According to publications and patent data, the results reveal a crucial R&D map of Germany until 2021.